Das sowjetische Speziallager Nr. 2 1945 - 1950: Katalog zur ständigen historischen Ausstellung - Ritscher, Bodo; Lüttgenau, Rikola-Gunnar; Hammermann, Gabriele; Röll, Wolfgang; Schölzel, Christian (Wallstein Verlag, 1999)
Katalog zur ständigen historischen Ausstellung